Rural development in the region of the Danube Delta: Strategies at European level and implementation at the national level - Ruxandra Eugenia Pop (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
The present paper aims to explore the contribution and implications of Romania to the development of the Danube region over the years, focusing on the interactions between internal and international factors. From the analyzed ones, we can affirm the fact that the internal factors play a secondary role in the development of the strategies, the majority role holding the international factors. Regarding the present and future strategies established at European level we can conclude that in their formulation the awareness should be extended to the perceptions of the local communities in the area, thus analyzing their identity, cultural heritage, economic and social potential of the analyzed areas. During the paper will analyze aspects such as: historical, geographical and socio-cultural context, the economic importance of the Danube in the European context, the European institutional framework for the international use of the Danube, the Strategy of the European Union at the level of the Danube region, national aspects related to the Danube Delta region.
Keywords: J18; Q38; Q58; 330; Romanian Danube region; capitalization of the potential of the Danube Delta region; identity of the Danube region